PROBLEMS OF INDUCED SEISMICITY AND ENGINEERING GEOLOGICAL PROTECTION OF RESERVOIRS OF THE BAIKALANGARA CASCADE - К. G. Levi; Е. А. Kozyreva; N. V. Zadonina; V. V. Chechelnitsky; N. A. Gilyova (Геодинамика и тектонофизика, 2015)
The paper presents results of analysis of induced seismicity and changes in processes related to engineering geology in coastal zones of reservoirs of the BaikalAngara cascade. It is proposed to establish a system for monitoring of geological and geophysical processes in order to avoid disturbances in the modes of operation of large hydrotechnical facilities and waterside structures.